ADAMTS13 content and VWF multimer and triplet structure in commercially available VWF/FVIII concentrates. Issue 2 (March 2015) - Kannicht, Christoph; Fisseau, Claudine; Hofmann, Werner; Kröning, Mario; Fuchs, Birte
Abstract: ADAMTS13 is a metalloproteinase that cleaves von Willebrand factor (VWF) into smaller multimers in vivo . This cleavage creates both the typical multimeric size distribution and the characteristic triplet band distribution of VWF. Here we analysed ADAMTS13 content, VWF multimeric size distribution and VWF triplet structure in five commercial VWF/factor VIII (FVIII) concentrates. The relative distribution of ADAMTS13 activity values corresponded well to the ADAMTS13 antigen values for all examined concentrates except Haemate HS ®, which had markedly higher ADAMTS13 antigen/activity ratio, with Fanhdi ® and Haemate HS ® displaying the most intense ADAMTS13 signal. Interestingly, ADAMTS13 levels did not correlate with the high molecular weight multimer content of the concentrates, but did correlate with VWF triplet distribution. Densitometric quantification showed that Wilate ®, Immunate ® and Willfact ® displayed human plasma-like VWF triplet distribution, whereas Fanhdi ® and Haemate HS ® showed enhanced content of the faster migrating triplet band, which corresponded well to their higher ADAMTS13 content. In summary, Immunate ®, Willfact ® and Wilate ® had lower levels of ADAMTS13 antigen and activity and exhibited a plasma-like VWF triplet structure. Fanhdi ® and Haemate HS ® had higher ADAMTS13 content and an altered triplet structure. The possible impact of these observations on function and clinical efficacy of VWF/FVIII concentrates is discussed.